You're the First One I've Told : The Faces of HIV in the Deep South - Whetten, Kathryn, 1963- (Book collections on Project MUSE., 2013)
The Deep South has seen a 36 percent increase in AIDS cases while the rest of the nation has seen a 2 percent decline. Many of the underlying reasons for the disease's continued spread in the region - ignorance about HIV, reluctance to get tested, non-adherence to treatment protocols, resistance to behavioral changes - remain unaddressed by policymakers. In this book, the authors present a discussion of twenty-five ethnographic life stories of people living with HIV in the South. Most importantly, they incorporate research from their quantitative study, "Coping with HIV/AIDS in the Southeast" (CHASE), which includes 611 HIV-positive patients from North Carolina, South Carolina, Georgia, Alabama, and Louisiana